2017
DOI: 10.6063/motricidade.12935
|View full text |Cite
|
Sign up to set email alerts
|

Technical and tactical performance indicators based on the outcome of the set in the school volleyball

Abstract: ARTIGO ORIGINAL | ORIGINAL ARTICLE RESUMOO objetivo do estudo foi identificar e comparar os indicadores de rendimento técnico-tático em função do resultado do set no voleibol feminino escolar. Participaram do estudo 110 atletas, com faixa etária entre 12 a 14 anos, pertencentes a 11 equipes. Foram filmados 58 sets de 28 jogos, e analisados 7194 ações, sendo 2830 saques, 2157 recepções de saque, 1358 levantamentos e 1299 ataques. Em seguida, os sets dos jogos foram agrupados em sets vencedores e perdedores. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…The same pattern was clearly observed in girls in the SU test, but in FAH, a mixed profile was expressed, with sibling girls showing higher values between 7 and 9 years of age while only child girls outperformed those with siblings in terms of physical growth. Indeed, Wrotniak et al ( 44 ) also concluded that motor proficiency was not related among siblings, while Costa et al ( 45 ) and Pereira et al ( 46 ) observed that only children and firstborn siblings showed greater strength values while exhibiting worse velocity and flexibility results. Such contradictory results confirm the need to conduct more studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…The same pattern was clearly observed in girls in the SU test, but in FAH, a mixed profile was expressed, with sibling girls showing higher values between 7 and 9 years of age while only child girls outperformed those with siblings in terms of physical growth. Indeed, Wrotniak et al ( 44 ) also concluded that motor proficiency was not related among siblings, while Costa et al ( 45 ) and Pereira et al ( 46 ) observed that only children and firstborn siblings showed greater strength values while exhibiting worse velocity and flexibility results. Such contradictory results confirm the need to conduct more studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo com atletas mais experientes, dificilmente o levantador consegue reverter recepções deficitárias com o levantamento28 . Para essa categoria, ainda não se exigem variações de distribuição, a fim de confundir o bloqueio29 .Logo, a excelência e erro são fatores discriminantes para vitória30 , deste modo, técnicos devem se atentar à precisão e à consistência para esse fundamento, além da qualidade da recepção de saque.Conforme as outras variáveis, o tipo de técnica utilizada no ataque também se associou à qualidade da ação (ꭕ 2 = 241,678; p<0,001; TE= 0,305; efeito grande) (Quadro 4). Desta forma, houve maior frequência de utilização das técnicas de corte com salto e sem salto (∑= 53,6%).…”
unclassified